Teacher's Attitude Toward Disciplinary Actions for School Children: Gender Perspective - Pokharel, Samidha Dhungel (Tribhuvan University Journal, 2013)
Gender discrimination is an emerging issue of an individual right after his/her birth. Intentional gender discrimination/ gender differentiated behavior can be seen and feel both in private and public life. This study aims to documents the teacher's gender differentiated behavior while disciplining the school children and to analyze the factors associated with such behavior. The study was designed as a descriptive study based on sample survey. The totals of 119 teachers from 60schools were randomly chosen as respondents at the time of school visit. The study reveals the different types of disciplinary actions used by male and female teachers for different reasons. Male teachers are more concerned with the sex of students than female teachers while applying disciplinary techniques. School boys are the victim of gender differentiated behavior of the teachers because of gender discriminatory perceptions.